2001
DOI: 10.1038/nn733
|View full text |Cite
|
Sign up to set email alerts
|

Responses of human frontal cortex to surprising events are predicted by formal associative learning theory

Abstract: Learning depends on surprise and is not engendered by predictable occurrences. In this functional magnetic resonance imaging (fMRI) study of causal associative learning, we show that dorsolateral prefrontal cortex (DLPFC) is associated specifically with the adjustment of inferential learning on the basis of unpredictability. At the outset, when all associations were unpredictable, DLPFC activation was maximal. This response attenuated with learning but, subsequently, activation here was evoked by surprise viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
165
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(192 citation statements)
references
References 28 publications
26
165
1
Order By: Relevance
“…The finding is consistent with other recently published studies (40,41) as well as with dopaminergic inputs to this region of the brain (42). Evaluation of expected reward level (equivalently, risk of the choice) may thus take place within this region of the brain, or may be carried out through interaction with other reward͞emotion-related structures to which it is connected (such as amygdala, basal ganglia, insula, and other sectors of PFC).…”
Section: Discussionsupporting
confidence: 93%
“…The finding is consistent with other recently published studies (40,41) as well as with dopaminergic inputs to this region of the brain (42). Evaluation of expected reward level (equivalently, risk of the choice) may thus take place within this region of the brain, or may be carried out through interaction with other reward͞emotion-related structures to which it is connected (such as amygdala, basal ganglia, insula, and other sectors of PFC).…”
Section: Discussionsupporting
confidence: 93%
“…Small action prediction errors allow the learning participant to reconfirm that they are engaging in the correct strategy without observing the outcome of the other player. The region of DLPFC where activity correlates most strongly with the expected action prediction error signal has previously been shown to respond to other types of prediction error (15), to conflict (16), and to trials that violate an expectancy that was learned from previous trials (17). The present finding also fits well with previous research implicating the DLPFC in action selection (18).…”
Section: Discussionsupporting
confidence: 90%
“…It is tempting to interpret these responses as relevant for the new learning that has to occur in this phase: while CSX (as part of CSAX) has to be established as nonpredictive for the US, CSY (as part of CSBY) has to be established as predictive for the US. Previous studies would support such an interpretation, linking dlPFC responses to accurate contingency tracking (Carter et al, 2006) and to unsigned prediction error signals as observed in causal learning studies (Fletcher et al, 2001;Turner et al, 2004). Yet, confounding factors such as stimulus novelty and stimulus complexity were also present on compound trials and could thus account for the increase in dlPFC activity (Turner et al, 2004).…”
Section: Discussionmentioning
confidence: 72%